The mediating role of social support in promoting physical activity among children in South Africa - Howard Gomwe; Lesego Phiri; Chioneso Show Marange (AOSIS, 2023)
Background: Low physical activity (PA) participation levels and increasing non-communicable diseases in children are concerning in South Africa and globally. Objectives: We sought to assess the mediating role of perceived social support factors on the relationship between PA enjoyment and PA levels among rural, peri-urban and urban school children. Method: A cross-sectional study was adopted to assess peer, family and teacher encouragement as mediators on the relationship between perceived PA enjoyment and perceived physical activity participation among children, using the Physical Activity Questionnaire for Older Children (PAQ-C). The sample comprised a random sample of primary school learners aged 9-14 years. Results: The sample consisted of 870 primary school learners with a mean age of 11.0 ± 1.49 years. Most participants were girls (n = 519; 59.7%). The findings suggest low levels of perceived PA participation (mean = 2.33, standard deviation [s.d.]: 0.43). Peer (β = 0.0187, 95% confidence interval [CI]: 0.0088, 0.0307), family (β = 0.0280, 95% CI: 0.0155, 0.0425) and teacher (β = 0.0242, 95% CI: 0.0127, 0.0378) encouragement partially mediates the relationship between perceived PA enjoyment and perceived PA participation. Family encouragement (β = 0.0158, 95% CI: 0.0017, 0.0311) has the most considerable mediating effect, followed by teacher encouragement (β = 0.0125, 95% CI: 0.0010, 0.0269). Conclusion: The findings demonstrated low levels of perceived PA participation in school learners. Therefore, we recommends including social factors as mediators in PA intervention programmes in primary schools. Clinical implications: Social support factors as mediators on the relationship between PA enjoyment and PA participation among children may improve children's PA participation levels and help prevent non-communicable diseases in future.